2019
DOI: 10.1021/acssensors.9b00992
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional NbS2 Gas Sensors for Selective and Reversible NO2 Detection at Room Temperature

Abstract: Transition metal dichalcogenides (TMDs) have attracted enormous attention in diverse research fields. Especially, gas sensors are considered in a promising application exploiting TMDs. However, the studies are confined to only major TMDs such as MoS 2 and WS 2 . Particularly, the chemoresistive sensing properties of two-dimensional (2D) NbS 2 have never been explored. For the first time, we report room temperature NO 2 sensing characteristics of 2D NbS 2 nanosheets and the sensing mechanisms using first-princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 59 publications
3
70
0
Order By: Relevance
“…Accordingly, although rGOs are more cost‐effective gas sensors than graphene, the humidity dependence of gas sensing characteristics should be suppressed for designing reliable rGO‐based artificial olfaction devices. Most TMDs, including MoS 2 , [ 547 ] WS 2 , [ 548–551 ] SnS 2 , [ 552 ] NbS 2, [ 553 ] are known for significant humidity dependence in their gas sensing characteristics. MoS 2 [ 554,555 ] and WS 2 [ 549,556 ] are also good humidity sensors.…”
Section: Reliable Sensing Materials For Artificial Olfactionmentioning
confidence: 99%
“…Accordingly, although rGOs are more cost‐effective gas sensors than graphene, the humidity dependence of gas sensing characteristics should be suppressed for designing reliable rGO‐based artificial olfaction devices. Most TMDs, including MoS 2 , [ 547 ] WS 2 , [ 548–551 ] SnS 2 , [ 552 ] NbS 2, [ 553 ] are known for significant humidity dependence in their gas sensing characteristics. MoS 2 [ 554,555 ] and WS 2 [ 549,556 ] are also good humidity sensors.…”
Section: Reliable Sensing Materials For Artificial Olfactionmentioning
confidence: 99%
“…Selectivity can be achieved through dedicated functionalization layers that enhance the reactivity only for certain gases. In addition to graphene, 2D materials such as MoS 2 [ 112 , 249 ], molybdenum diselenide (MoSe 2 ) [ 110 , 250 ], molybdenum ditelluride (MoTe 2 ) [ 251 ], tungsten diselenide (WS 2 ) [ 117 ], niobium diselenide (NbS 2 ) [ 252 ], rhenium disulfide (ReS 2 ) [ 253 ], or platinum diselenide (PtSe 2 ) [ 119 ] have been shown to possess high gas and chemical sensor performance. Some TMD materials even show quite specific sensing behavior; in particular, PtSe 2 has been shown to have a high selectivity towards NO 2 , which also was validated theoretically [ 119 ].…”
Section: Gas Sensorsmentioning
confidence: 99%
“…In addition to MoS 2 , other layered pristine TMDCs were employed for gas sensing and studies have demonstrated WS 2 [94], MoSe 2 [13,41], WSe 2 [95][96][97][98], MoTe 2 [42,43,99,100], and NbS 2 [101] can be used in FET for the detection of O 2 , NO, NO 2 , SO 2 , etc., with a sensing capability of ppm to ppb level. Studies on MoSe 2 FET sensor suggest that gap state variation is the key mechanism in NO 2 sensing based on modeling and quantum transport simulation.…”
Section: Gas Sensingmentioning
confidence: 99%